Rural Identity as a Contributing Factor to Anti-Intellectualism in the U.S - Lunz Trujillo, Kristin (Political behavior, 2022)
Anti-intellectualism—a distrust of intellectuals and experts—has had a significant political presence in the U.S. and globally, especially in recent years. Anti-intellectualism drives support for phenomena such as populism, a rejection of scientific consensus, and health and science misinformation endorsement. Therefore, discovering what drives someone to be more anti-intellectual is highly important in understanding contemporary public opinion and political behavior. Here, I argue that a significant and overlooked factor contributing to anti-intellectualism is rural social identification—a psychological attachment to being from a rural area or small town—because rural identity in particular views experts and intellectuals as an out-group. Using 2019 ANES pilot data (N = 3000), original survey data (N = 811) and a separate original survey experiment, I find that rural social identification significantly predicts greater anti-intellectualism. Conversely, anti-intellectualism is not significantly associated with rural residency alone, as theoretically speaking, simply living in a rural area does not capture the affective dimension of rural psychological attachment. These findings have implications for health and science attitudes, populist support, and other relevant political matters. They also have implications for what it means to hold a rural identity beyond anti-urban sentiment, and for understanding the urban–rural divide.